iTRAQ-Based Quantitative Proteomics and Transcriptomics Provide Insights Into the Importance of Expansins During Root Development in Carrot - Wang, Ya-Hui; Que, Feng; Wang, Guang-Long; Hao, Jian-Nan; Li, Tong; Xu, Zhi-Sheng; Xiong, Ai-Sheng (Frontiers in Genetics, 2019)
Abstracts Carrot is an important root vegetable crop with a variety of nutrients. As the main product of carrots, the growth and development of fleshy roots directly determine the yield and quality of carrots. However, molecular mechanism underlying the carrot root formation and expansion is still limited. In our study, isobaric tags for relative and absolute quantification (iTRAQ) was utilized to explore the differentially expressed proteins (DEPs) during different developmental stages of carrot roots. Overall, 2,845 proteins were detected, of which 118 were significantly expressed in all three stages. DEPs that participated in several growth metabolisms were identified, including energy metabolism, defense metabolism, cell growth and shape regulation. Among them, two expansin proteins were obtained. A total of 30 expansin genes were identified based on the carrot genome database. Structure analysis showed that carrot expansin gene family was relatively conserved. Based on the expression analysis, we found that the expression profile of expansins genes was up-regulated during the vigorous growing period of carrot root. Furthermore, there was a consistent relationship between the expression patterns of mRNA and protein. The results indicated that expansin proteins might play important roles during root development in carrot. Our work provided useful information for understanding molecular mechanism of carrot root development.